Mandarin–English speaking bilingual and Mandarin speaking monolingual children's comprehension of relative clauses. (26th April 2019) - Tsoi, Elaine Yee Ling; Yang, Wenchun; Chan, Angel; Kidd, Evan
Abstract: The current study investigated the comprehension of subject and object relative clauses (RCs) in bilingual Mandarin–English children ( N = 55, M age = 7 years, 5 months [7;5], SD = 1;8) and language-matched monolingual Mandarin-speaking children ( N = 59, M age = 5;4, SD = 0;7). The children completed a picture-referent selection task that tested their comprehension of subject and object RCs, and standardized assessments of vocabulary knowledge. Results showed a very similar pattern of responding in both groups. In comparison to past studies of Cantonese, the bilingual and monolingual children both showed a significant subject-over-object RC advantage. An error analysis suggested that the children's difficulty with object RCs reflected the tendency to interpret the sentential subject as the head noun. A subsequent corpus analysis suggested that children's difficulty with object RCs may be in part due to distributional information favoring subject RC analyses. Individual differences analyses suggested crosslinguistic transfer from English to Mandarin in the bilingual children at the individual but not the group level, with the results indicating that comparative English dominance makes children vulnerable to error.